2013
DOI: 10.1371/journal.pone.0077915
|View full text |Cite
|
Sign up to set email alerts
|

Extracts of Pomelo Peels Prevent High-Fat Diet-Induced Metabolic Disorders in C57BL/6 Mice through Activating the PPARα and GLUT4 Pathway

Abstract: ObjectiveMetabolic syndrome is a serious health problem in both developed and developing countries. The present study investigated the anti-metabolic disorder effects of different pomelo varieties on obese C57BL/6 mice induced by high-fat (HF) diet.DesignThe peels of four pomelo varieties were extracted with ethanol and the total phenols and flavonoids content of these extracts were measured. For the animal experiment, the female C57BL/6 mice were fed with a Chow diet or a HF diet alone or supplemented with 1%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 35 publications
1
33
0
Order By: Relevance
“…SIRT1 regulates the expression of peroxisome proliferators activated receptor (PPAR)-α, a key factor in the regulation of lipid metabolism [15,16] . However, to our knowledge, there are few studies regarding the effect of lutein supplements on SIRT1 and PPAR-α.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…SIRT1 regulates the expression of peroxisome proliferators activated receptor (PPAR)-α, a key factor in the regulation of lipid metabolism [15,16] . However, to our knowledge, there are few studies regarding the effect of lutein supplements on SIRT1 and PPAR-α.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies have demonstrated that PPAR-α plays an important role in the regulation of hepatic lipid metabolism [15,32] and that the inhibition of PPAR-α might induce hepatic steatosis [33] . Thus, we tested the protein level of PPAR-α and found that HFD feeding significantly inhibited the expression of PPAR-α, and that lutein supplementation reversed such inhibition effectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ding et al found that extracts of pomelo peels blocked the body weight gain, lowered fasting blood glucose, serum total cholesterol, liver lipid levels, and improved glucose tolerance and insulin resistance, It can also lowered serum insulin levels in HF diet-fed mice (43). Panax notoginseng saponins, the principal ingredients extracted from the traditional Chinese medicinal herb Panax notoginseng, exhibited a considerable anti-obesity action, significantly increase insulin sensitivity and improve glucose homeostasis in KK-Ay mice which is clinically significant for the management of diabetes.…”
Section: Reducing Blood Sugar and Insulin Resistancementioning
confidence: 99%